A Novel Role of Growth Differentiation Factor (GDF)-15 in Overlap with Sedentary Lifestyle and Cognitive Risk in COPD - Hirano, Tsunahiko; Doi, Keiko; Matsunaga, Kazuto; Takahashi, Shun; Donishi, Tomohiro; Suga, Kazuyoshi; Oishi, Keiji; Yasuda, Kasumi; Mimura, Yusuke; Harada, Misa; Suizu, Sumiteru; Murakawa, Keita; et al. (Journal of clinical medicine, 2020)
Sedentary behavior and cognitive impairment have a direct impact on patients’ outcomes. An energy metabolic disorder may be involved in the overlap of these comorbid conditions (motoric cognitive risk (MCR)) in patients with chronic obstructive pulmonary disease (COPD). We aimed to explore the linkage between a proapoptotic protein, growth differentiation factor (GDF)-15, and MCR. Physical activity (PA), cognitive function (Japanese version of the Montreal Cognitive Assessment: MOCA-J), and the serum GDF-15 levels were assessed in healthy subjects (n = 14), asthmatics (n = 22), and COPD patients (n = 28). In the entire cohort, serum GDF-15 had negative correlations with exercise (Ex) (ρ = −0.43, p < 0.001) and MoCA-J (ρ = −0.44, p < 0.001), and Ex and MOCA-J showed a positive correlation (ρ = 0.52, p < 0.0001). Compared to healthy subjects and asthmatics, COPD patients showed the highest serum GDF-15 levels and had a significantly higher proportion of subjects with MCR (both sedentary lifestyle (EX < 1.5) and cognitive risk (MoCA-J ≤ 25)). Also, we found that serum GDF-15 has a screening potential (100% sensitivity) greater than aging (67% sensitivity) for detecting MCR in COPD patients. In conclusion, higher serum GDF-15 had interrelationships with a sedentary lifestyle and cognitive risk. This protein was not disease-specific but could be a screening biomarker to detect MCR related to poor health outcomes of COPD patients.